Studi Timbulan Dan Komposisi Sampah Non Domestik Wilayah Pengembangan IV Kota Pekanbaru - Grethy Asmara Sitorus; Elvi Yenie; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study aims to analyze the data on the generation and composition of non-domestic waste in development area IV Pekanbaru City. Generation sampling based on SNI 19-3964-1994 which was carried out for eight consecutive days with a total sample of 114 unit. The total result of non-domestic waste generation is 0,064 kg/person/day or 0,335 l/person/day. The composition of non domestic waste includes food waste, paper, plasti, cloth/textiles, rubber/leather, yard waste, wood, glass, metal, and other waste. Keywords: Generation, Composition, Non domestic.